A prospective study to compare serial changes in pain scores for patients with and without a history of frequent ED utilization. Issue 6 (June 2021) - Joseph, Ryan; Tomanec, Alainya; McLaughlin, Thomas; Guardiola, Jose; Richman, Peter
Abstract: Background: In the face of the opiate addiction epidemic, there is a paucity of research that evaluates limitations for our current pain rating methodologies for patient populations at risk for drug seeking behavior. Objective: We hypothesized that VAS scores would be higher and show less serial improvement for patients with a history of frequent ED use. Methods: This was a prospective, observational cohort study of a convenience sample of adult ED patients with chief complaint of pain. Initial VAS scores were recorded. Pain scores were subsequently updated 30–45 min after pain medication administration. ED frequenter defined as having >4 ED visits over a 1-year time period. Categorical data analyzed by chi-square; continuous data analyzed by t-tests. A multiple linear regression performed to control for confounding. Results: 125 patients were enrolled; 51% ED frequenters. ED frequenters were similar to non-ED frequenters with respect to gender, mean age, Hispanic race, educational level, chief complaint type, and initial pain medication narcotic. ED frequenters more likely to have higher initial VAS score (9.17+/-1.25 vs. 8.51+/-1.68; p = 0.01) and higher second VAS scores (7.48+/-2.56 vs. 5.00+/-3.28; p <0.001) and significantly lower mean change in first to second VAS scores (1.69+/-2.17 vs. 3.51+/-3.25; p <0.001). Within our multiple linear regression model, only ED frequenter group (p < 0.001) and private insurance status (0.04) were associated with differences in mean reduction in pain scores. Conclusion: We found that ED frequenters had significantly less improvement between first and second VAS measurements. Abstract : Pain; Analgesics; Visual analog scale; Pain scores; Pain medications; Emergency department; Opioids; Opioid epidemic; Patient satisfaction